Outcome of Crizotinib Treatment in a Young Woman with Heavily Pretreated ROS1-positive Lung Cancer. Issue 3 (May 2015) - Petreni, Paolo; Mazzoni, Francesca; Meoni, Giulia; Lunghi, Alice; Cecere, Fabiana Letizia; Muto, Andrea; Di Costanzo, Francesco
Non-small-cell lung cancer is a term that encompasses a number of subtypes of lung cancer. In recent years, several intracellular pathways have been studied in order to discover a potential target for novel anticancer therapies such as anaplastic lymphoma kinase (ALK) and reactive oxygen species 1 (ROS1). Increased interest in oncologic treatment research has resulted from the observation that ALK- and ROS1-associated tyrosine kinases show molecular analogies in some of their domains. This discovery led to the hypothesis that target therapy against ALK translocation could have efficacy also in ROS1-positive tumors. Crizotinib is an oral tyrosine kinase inhibitor that binds the ALK tyrosine kinase domain, blocking its function. We report the case of a woman with heavily pretreated metastatic lung adenocarcinoma harboring ROS1 positivity who experienced a prolonged and dramatic clinical benefit from crizotinib therapy.